Sartrean Existentialism and Abner’s Odyssey for Self-identity in Faulkner’s Writings - Dangaura, Mohan (BMC Research Journal, 2025)
This essay examines Abner Snopes; one of the most distinct character in William Faulkner’s writings and major character in his short story “Barn Burning” from Jean-Paul Sartre’s perspective on existentialism. Sartre defines human exploration of personal identity as swaying movement between being and becoming. Studying Faulkner’s Abner from Sartre’s philosophy helps to understand the general human tendency of struggling to achieve one’s true self. Abner as an uncompromising foe in “Barn Burning,” creates suffering to his employers and disapproves the actions of his own relatives. His fury drives him to continue damaging other people’s property. His fury provoke him to burn his master’s barn in retaliation. Even after repeated attempts, Abner’s odyssey for achieving the social acceptance and dignity fail. Realizing his place in society is still his unfulfilled ambition; his spirit wobbles between being himself and conforming to societal standards. Therefore, study of Abner’s personality through Sartrean existentialism helps us to understand not only the particular fictional individual but dominant existential crisis among all of us. Hence, this essay attempts to explain the ways an individual’s character and identity gets shaped by his wobbling quest of being and becoming in society by taking Abner’s case as the point of critical analysis.